Mechanical Behavior of Reactive Powder Concrete Made From Local Material Subjected to Axial Pressure - Ji, Jing; Kang, Wei; Jiang, Liangqin; Li, Yunhao; Ren, Hongguo; Hao, Sixue; He, Lingjie; Lin, Yubo; Yu, Chenyu (Frontiers in Materials, 2021)
In order to investigate the influence of various parameters on the compressive strength and fluidity of reactive powder concrete (RPC) made from local materials, 22 groups of RPC cubic specimens and 3 groups of RPC prism specimens were designed, and the main parameters included water to binder ratio, the ratio of silica fume to cement, the ratio of slag powder to cement, the ratio of quartz sand to cement, volume fraction of steel fiber and steam curing time. The stress-strain curves and failure mode of RPC cubic specimens were obtained by axial compression test. The influence of various parameters on the compressive mechanical properties and the mixture fluidity of RPC cubic specimens was analyzed. The results show that the ultimate compressive strength (fcu) of RPC decreases gradually with the increasing of water to binder ratio, however fcu increases with the increasing of volume fraction of steel fiber. fcu increases firstly and then decreases with the increasing of the ratio of silica fume to cement, the ratio of slag powder to cement and the ratio of quartz sand to cement, so there exists a peak point. The fluidity of RPC mixture increases with the increasing of water to binder ratio and the ratio of slag powder to cement, on the contrary, it decreases with the increasing of the ratio of silica fume to cement, the ratio of quartz sand to cement and volume fraction of steel fiber. Based on the analysis of the parameters, the optimal mix proportion of the RPC made from local materials is proposed. The constitutive model of RPC is established according to the stress-strain curves of RPC prism specimens. Finally, the relationship between compressive strength and elastic modulus of RPC made of local materials is regressed statistically.